Database Archiving - Olson, Jack (Elsevier, 2011)
With the amount of data a business accumulates now doubling every 12 to 18 months, IT professionals need to know how to develop a system for archiving important database data, in a way that both satisfies regulatory requirements and is durable and secure. This important and timely new book explains how to solve these challenges without compromising the operation of current systems. It shows how to do all this as part of a standardized archival process that requires modest contributions from team members throughout an organization, rather than the superhuman effort of a dedicated team.